Assessment of Learning Outcomes in Higher Education Cross-National Comparisons and Perspectives (Methodology of Educational Measurement and Assessment, 2018)
This book offers a comprehensive overview of current, innovative approaches to assessing generic and domain-specific learning outcomes in higher education at both national and international levels. It discusses the most significant initiatives over the past decade to develop objective, valid, and reliable assessment tools and presents state-of-the-art procedures to adapt and validate them for use in other countries. The authors highlight key conceptual and methodological challenges connected with intra-national and cross-national assessment of learning outcomes in higher education; introduce novel approaches to improving assessment, evaluation, testing, and measurement practices; and offer exemplary implementation frameworks. Further, they examine the results of and lessons learned from various recent, world-renowned research programs and feasibility studies, and present results from their own studies to provide new insights into how to draw valid conclusions about learning outcomes achieved in various contexts. .